bonjour,
a) ( - 3 x + 1 ) ( 3 x - 1 ) = - 9 x² + 3 x + 3 x - 1 = - 9 x² + 6 x - 1
b) ( 4 - 7 x ) ( 4 + 7 x ) = 16 - 49 x² identité
c) ( 2 x - 5 ) ( 2 x - 5 ) = ( 2 x - 5 )² = 4 x² - 20 x + 25 identité
d) ( 8 - 2 x )² - ( 2 + 2 x ) ( 2 - 2 x ) = 64 - 32 x + 4 x² - ( 4 - 4 x² )
= 4 x² + 64 - 32 x - 4 + 4 x² = 8 x² - 32 x + 60
e) - ( 3 a - 4 b ) ( 2 a + b)²
= - ( 3 a - 4 b) ( 4 a² + 4 ab + b² )
= - ( 12 a ³ + 12 a²b + 3 ab² - 16 a²b - 16 ab² - 4 ab² - 4 b ³)
= - ( 12 a ³ - 4 a²b - 17 ab² - 4 b³)
= - 12 a³ + 4 a²b + 17 ab² + 4 b³